Impact of Worker’s Remittance on Financial Development of Nepal - Thapa, Srijana; Adhikari Thapa, Kalpana (Baneshwor Campus Journal of Academia, 2023)
This study analyzes the impact of remittance inflows on financial development of Nepal. Money supply and total bank deposits are selected as the dependent variables while remittance inflow as an increment of GDP, foreign direct investment as an increment of GDP, inflation, per capita income and exchange rate are selected as independent variables. The key sources of data include Quarterly Economic Bulletin published by Nepal Rashtrabank, Economic Survey published by Ministry of Finance and World Development Indicators of World Bank. The study is grounded on the secondary data which are collected for the period of 31 years from 1990 to 2021. The co-integration analysis has been performed to analyze the long run co-integrating relationship between remittance and financial development. It is found that there is long run co-integrating relationship between financial development and remittance inflow in Nepal. In addition, remittance inflow has long run positive relationship with total deposits. This indicates that higher the remittance inflow, higher would be the total deposits. The findings also show that per capita income, inflation and exchange rate has positive relationship with total deposit and money supply. This indicates that increase per capita income leads to increase in total deposits and money supply in long run. Likewise, the study indicates that higher the inflation in long run, higher would be the total deposits and money supply. The result of Granger Causality shows that there is unidirectional causality from remittance to total deposits and money supply. This indicates that remittance leads to increase in total deposits and the money supply in Nepal.